Tear-resistant high-toughness functional polyester film and preparation process thereof

By preparing copolyester particles, toughening layer, tear-resistant layer and interface bonding layer in polyester film, the problem of insufficient toughness of traditional polyester films is solved, and the tear-resistant properties and toughness of the film are significantly improved.

CN120082084AActive Publication Date: 2025-06-03FOSHAN SAIHE FILM TECH CO LTD

Patent Information

Application Number
CN202510353007.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-06-03
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

During the production, assembly and use of optical equipment, traditional polyester films are prone to cracking or fine cracks due to insufficient toughness, which affects the display effect and reduces the product yield.

Method used

The substrate layer was obtained by melting and extruding the copolyester particles with triphenyl phosphate and tris(2,4-di-tert-butylphenyl)phosphite and quenching treatment, and a toughening layer was formed by combining polyurethane prepolymer, core-shell toughening agent and photoinitiator. A composite system of aramid nanofibers and modified carbon nanotubes was used to form a tear-resistant layer by electrospinning, and an interface bonding layer was formed by isocyanate prepolymer, silane coupling agent and nanosilica sol.

Benefits of technology

It significantly improves the toughness of polyester films, can effectively resist mechanical stress, delay material failure process, and improve product quality and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120082084A_ABST
    Figure CN120082084A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of film products, in particular to a tear-resistant high-toughness functional polyester film and a preparation process thereof. The problem that a polyester film is poor in toughness is solved. The preparation method comprises the following steps: preparing copolyester particles, carrying out melt extrusion on the copolyester particles, triphenyl phosphate and tris (2, 4-di-tert-butylphenyl) phosphite, and carrying out shock cooling treatment to obtain a base material layer; the method comprises the following steps: preparing a core-shell toughening agent, mixing the core-shell toughening agent with a polyurethane prepolymer and a photoinitiator, and coating the mixture on the surface of a base material layer to obtain a toughening layer; surface grafting carbon nanotubes are prepared and form a composite system with sulfuric acid swelling aramid nanofibers, and an anti-tearing layer is formed through an electrostatic spinning process; mixing an isocyanate prepolymer, a silane coupling agent and nano silica sol, spraying the mixture on the surface of the tear-resistant layer, and performing in-situ polymerization and post-curing to obtain an interface bonding layer; the prepared polyester film has excellent toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thin film products, and particularly to a tear-resistant and high-toughness functional polyester film and a preparation process thereof. Background Art

[0002] Due to its good comprehensive properties, such as mechanical properties, optical properties, chemical stability, etc., the laminated film composed of polyester is widely used in many fields such as packaging, electronics, and optics. For example, in liquid crystal displays (LCDs) and organic light-emitting diode displays (OLEDs), the polyester film serves as the support material and protective film for polarizers, playing an indispensable role in maintaining the stability and clarity of the display effect; in the manufacture of optical lenses, the polyester film is used for the packaging and protection of lenses to prevent the lenses from being scratched.

[0003] However, with the rapid development of optical technology, more stringent requirements are put forward for the performance of polyester films. During the production, assembly, and daily use of optical devices, polyester films often face various mechanical stresses. For example, in the process of laminating polarizers, the polyester film needs to be accurately and tightly laminated on other optical components. In this process, if the toughness of the film is insufficient, it is extremely easy to produce cracks or fine cracks due to stretching and bending, which not only affects the performance of the polarizer, but may also cause defects in the entire display module, reducing the product yield; in some wearable optical devices, due to the frequent bending and twisting of the device with the movement of the human body, the poor tear resistance and low toughness of traditional polyester films make it difficult to withstand these complex mechanical deformations, greatly limiting the innovative development of optical devices in the direction of miniaturization and flexibility.

[0004] Therefore, developing a functional polyester film with high toughness is of great practical significance for promoting technological progress in the optical field and improving product quality and reliability. For this reason, a tear-resistant and high-toughness functional polyester film and a preparation process thereof are proposed. Summary of the Invention

[0005] The purpose of the present invention is to provide a tear-resistant and high-toughness functional polyester film and a preparation process thereof. By preparing copolyester particles, melting and extruding them with triphenyl phosphate and tris(2,4-di-tert-butylphenyl) phosphite, and then performing quenching treatment to obtain a base material layer; by preparing a core-shell toughening agent, mixing it with a polyurethane prepolymer and a photoinitiator, and coating it on the surface of the base material layer to obtain a toughening layer; by preparing surface-grafted carbon nanotubes, forming a composite system with sulfuric acid-swollen aramid nanofibers, and forming a tear-resistant layer through an electrospinning process; by mixing an isocyanate prepolymer, a silane coupling agent, and nano-silica sol, spraying them on the surface of the tear-resistant layer, and performing in-situ polymerization and post-curing to obtain an interfacial bonding layer; the prepared polyester film has excellent toughness.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] It should be noted that all parts in the present invention are parts by mass.

[0008] On the one hand, the present invention provides a preparation process for an anti - tear and high - toughness functional polyester film. The preparation method is as follows: Melt - extrude copolyester particles, triphenyl phosphate, and tris(2,4 - di - tert - butylphenyl) phosphite, and then rapidly cool through a cooling roller to obtain a base material layer; Use a gravure coater to coat a mixed solution of polyurethane prepolymer, core - shell toughening agent, and photoinitiator on the surface of the base material layer to obtain a toughening layer; Perform electrospinning on the surface of the toughening layer to obtain an anti - tear layer; Use a high - pressure spray gun to evenly spray the prepolymer mixed solution on the surface of the anti - tear layer to obtain an interface bonding layer. Then, preheat on a preheating roller at 95°C for 3 min, followed by longitudinal stretching and transverse stretching, and finally high - temperature shaping and cooling winding to obtain the polyester film;

[0009] The copolyester particles are prepared from 1,4 - cyclohexanedimethanol, 2,6 - naphthalenedicarboxylic acid, and terephthalic acid;

[0010] The prepolymer mixed solution is prepared from isocyanate prepolymer, silane coupling agent KH550, and nano - silica sol.

[0011] Preferably, the preparation process of the base material layer is as follows: Put the copolyester particles into a vacuum oven at 120°C and dry for 4 h to obtain dried copolyester. Then, add the dried copolyester, 0.3 part of triphenyl phosphate, and 0.1 part of tris(2,4 - di - tert - butylphenyl) phosphite into a twin - screw extruder for melt - extrusion to obtain a melt; The temperature of the die head section of the twin - screw extruder is 290 - 320°C; Quench the melt through a cooling roller at 30°C to obtain a base material layer with a thickness of 80 μm.

[0012] Preferably, the preparation process of the copolyester particles is as follows: Add 12 parts of 1,4 - cyclohexanedimethanol, 15 parts of 2,6 - naphthalenedicarboxylic acid, and 73 parts of terephthalic acid into a reaction kettle, and introduce nitrogen into the reaction kettle. Heat up to 180 - 200°C and react for 2.5 h to obtain a pre - esterification product; Continue to heat up to 250 - 280°C, and at the same time reduce the pressure in the reaction kettle to 1 - 10 Pa, and react for 4 h to obtain a polycondensation product; Cool the polycondensation product into strips through a casting machine, and then cut it into particles through a granulator to obtain copolyester particles.

[0013] Preferably, the preparation process of the toughening layer is as follows: Stir - mix 70 - 85 parts of polyurethane prepolymer and 10 - 25 parts of core - shell toughening agent at 90°C for 30 min, add 3 parts of photoinitiator, and then perform ultrasonic dispersion to obtain a mixed solution. Use a gravure coater to coat the mixed solution on the surface of the base material layer, with a coating thickness of 20 μm. Then, under a wavelength of 365 nm and an intensity of 80 mW / cm 2Under the condition of , ultraviolet curing was carried out for 2 min, and then it was cured in an oven at 60 °C for 1 h to obtain the toughening layer.

[0014] Preferably, the preparation process of the core-shell toughening agent is as follows: Under nitrogen protection, 45 parts of methyl methacrylate, 1.5 parts of divinylbenzene and 120 parts of deionized water were mixed, pre-emulsified at 60-80 °C for 30 min, 0.7 part of potassium persulfate initiator was added, the temperature was raised to 75 °C and reacted for 4 h to obtain a poly(methyl methacrylate) core emulsion; the poly(methyl methacrylate) core emulsion was diluted to a solid content of 10%, 12 parts of glycidyl methacrylate and 7 parts of styrene were added and reacted for 30 min, potassium persulfate initiator was added dropwise, and after reacting at 70-95 °C for 6 h, it was centrifuged, washed and dried to obtain the core-shell toughening agent.

[0015] Preferably, the preparation process of the tear-resistant layer is as follows: 10-15 parts of aramid nanofibers were swollen in 98 wt% concentrated sulfuric acid for 30 min, and washed with deionized water to neutrality to obtain sulfuric acid-swollen aramid nanofibers; 5-10 parts of modified carbon nanotubes, sulfuric acid-swollen aramid nanofibers and 0.6 part of sodium dodecylbenzenesulfonate were added to 80 parts of N-methylpyrrolidone, and ball-milled and dispersed for 4 h to obtain a spinning solution; electrospinning was carried out on the surface of the toughening layer under the conditions of a voltage of 17-25 kV, a receiving distance of 15 cm, and a solution flow rate of 0.8 mL / h to obtain the tear-resistant layer.

[0016] Preferably, the preparation process of the modified carbon nanotubes is as follows: 15 parts of multi-walled carbon nanotubes were added to 30 wt% phosphoric acid solution, ultrasonically treated in a constant temperature water bath at 60 °C for 2 h, and then washed and dried with deionized water to obtain phosphorylated carbon nanotubes; 60 parts of dimethyl terephthalate and 38 parts of 1,4-butanediol were added to a three-necked flask, heated to 180 °C under nitrogen protection, 0.5 part of tetrabutyl titanate catalyst was added and reacted for 2 h, then the temperature was raised to 230-255 °C, the vacuum was reduced to 50 Pa, and the reaction was continued for 3 h, 1.2 parts of terminator ethylene glycol monomethyl ether was added, and reacted at 230 °C for 40 min to obtain a hydroxyl-terminated polyester oligomer; 30 parts of the hydroxyl-terminated polyester oligomer was dissolved in 200 parts of xylene, 10 parts of phosphorylated carbon nanotubes were added, ultrasonically dispersed at 120 °C for 1 h, 0.5 part of dicyclohexylcarbodiimide was added, the temperature was raised to 160 °C, and stirred under nitrogen protection for 6 h to obtain a reaction solution; the reaction solution was hot-filtered through a 0.45 μm filter membrane, washed 3 times with xylene and acetone in turn to remove unreacted oligomers, and vacuum dried at 60 °C for 12 h to obtain the modified carbon nanotubes.

[0017] Preferably, the preparation process of the interfacial bonding layer is as follows: Mix the isocyanate prepolymer, silane coupling agent KH550, and nano-silica sol evenly according to a mass ratio of 7.5:1.5:1 - 4 to obtain a prepolymer mixture; Use a high-pressure spray gun to evenly spray the prepolymer mixture on the surface of the tear-resistant layer, and the spraying amount is 7 - 11 g / m 2 , then carry out in-situ polymerization at 50 °C for 20 min, and finally post-cure in an oven at 75 °C for 20 - 50 min to form an interfacial bonding layer with a thickness of 100 nm.

[0018] Preferably, the draw ratio of longitudinal stretching is 3.8, the temperature is 105 °C, and the rate is 300% / min; the draw ratio of transverse stretching is 4.3, the temperature is 115 °C, and the rate is 280% / min; the high-temperature setting temperature is 180 °C, and the time is 8 min; for cooling and winding, first cool down to 100 °C at a rate of 5 °C / min, then carry out water cooling at room temperature, and the winding tension is 2.5 N / cm 2 .

[0019] On the other hand, the present invention provides a tear-resistant and high-toughness functional polyester film, which is composed of a base material layer, a toughening layer, a tear-resistant layer, and an interfacial bonding layer; the polyester film is prepared by the preparation process of any one of the above.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0021] 1. The base material layer of the present invention consists of a copolyester main chain composed of rigid 2,6-naphthalenedicarboxylic acid and flexible 1,4-cyclohexanedimethanol, forming an alternating distribution of ordered crystalline regions and amorphous regions, endowing the film with intrinsic tear resistance; the molecular chain packing of the naphthalene ring structure enhances rigidity and resists crack propagation caused by external forces; the helical conformation of the cyclohexane unit provides molecular chain ductility, dissipates energy through local slip, prevents brittle fracture, and improves the toughness of the film; the phosphate stabilizer optimizes the melt fluidity, inhibits processing defects, and the quenching process refines the crystal size and reduces structural weak points.

[0022] 2. The toughening layer of the present invention forms a dynamic cross-linked polyurethane network through photocuring, which has self-adaptive resilience, and the introduction of the core-shell toughening agent further enhances the energy absorption efficiency. When the film is subjected to external forces, the reversible extension and fracture of the polyurethane molecular chains can consume a large amount of energy, and the core-shell structure synergistically dissipates energy through shell layer fracture and core body plastic deformation, delaying the material failure process; the dynamic cross-linked structure releases internal stress through bond reconstruction during repeated bending, avoiding the accumulation of permanent microdamage and endowing the film with excellent toughness.

[0023] 3. The anti - tearing layer of the present invention adopts a composite system of aramid nanofibers and carbon nanotubes grafted on the surface, and constructs a highly oriented nanofiber network through the electrospinning process. The high specific surface area of nanoscale aramid fibers enhances the interfacial bonding force and forms a continuous force - transmission path; the grafted hydroxyl groups of modified carbon nanotubes with polyester oligomers enable them to be evenly dispersed and penetrate into the fiber gaps, inhibiting the spread of micro - damage through crack bridging and pull - out effects; at the same time, the nanoscale reinforcing agents significantly reduce the density of the material, endowing the film with the characteristics of co - existing lightweight and high strength without significantly increasing the thickness. This nano - synergistic reinforcement mechanism significantly improves the toughness of the polyester film.

[0024] 4. The interface bonding layer of the present invention significantly improves the interlayer bonding efficiency through a multi - level chemical cross - linking and nano - reinforcement strategy. The isocyanate prepolymer forms a dense covalent network with the hydroxyl groups on the surface of the anti - tearing layer, anchoring the reinforcing phase and the matrix to prevent failure caused by interface peeling; the silane coupling agent further bridges the inorganic nano - silica sol and the organic phase, constructing a molecular - level interpenetrating structure through in - situ condensation reaction to disperse local stress; the nano - silica sol fills the interface micropores and forms a physical interlock to delay the crack propagation rate when the crack crosses the interface; the dynamic cross - linking system endows the interface with self - adaptive deformation ability, consuming energy through bond reconstruction under external force to avoid delamination caused by stress concentration and improving the toughness of the polyester film. Description of the Drawings

[0025] Figure 1 It is a graph showing the toughness test results of Example 3, Examples 5 - 7 and Comparative Examples 4 - 7 of the present invention. Detailed Embodiments

[0026] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0027] Please refer to Figure 1 , the present invention provides an anti - tearing and highly - tough functional polyester film and its preparation process, and the technical solutions are as follows:

[0028] The substances involved in the present invention are as follows:

[0029] 1,4 - cyclohexanedimethanol CAS: 105 - 08 - 8; 2,6 - naphthalenedicarboxylic acid CAS: 1141 - 38 - 4; triphenyl phosphate CAS: 115 - 86 - 6; tris(2,4 - di - tert - butylphenyl) phosphite CAS: 31570 - 04 - 4; methyl methacrylate CAS: 80 - 62 - 6; divinylbenzene CAS: 1321 - 74 - 0; potassium persulfate CAS: 7727 - 21 - 1; glycidyl methacrylate CAS: 106 - 91 - 2; styrene CAS: 100 - 42 - 5; polyurethane prepolymer (molecular weight 3000 g / mol) CAS: 103837 - 45 - 2; photoinitiator Irgacure 184 CAS: 947 - 19 - 3; multi - walled carbon nanotubes CAS: 1333 - 86 - 4; dimethyl terephthalate CAS: 120 - 61 - 6; 1,4 - butanediol CAS: 110 - 63 - 4; tetrabutyl titanate CAS: 5593 - 70 - 4; ethylene glycol monomethyl ether CAS: 109 - 86 - 4; xylene CAS: 1330 - 20 - 7; dicyclohexylcarbodiimide CAS: 538 - 75 - 0; sodium dodecylbenzenesulfonate CAS: 25155 - 30 - 0; N - methylpyrrolidone CAS: 872 - 50 - 4; silane coupling agent KH550 CAS: 919 - 30 - 2; isocyanate prepolymer Desmodur N3300 was purchased from Guangzhou Haoyi New Material Technology Co., Ltd.; nano - silica sol was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; aramid nanofibers were prepared by the method described in Patent CN115652465B.

[0030] Example 1

[0031] Add 12 parts of 1,4 - cyclohexanedimethanol, 15 parts of 2,6 - naphthalenedicarboxylic acid and 73 parts of terephthalic acid into the reaction kettle, and introduce nitrogen into the reaction kettle. Heat up to 180 °C and react for 2.5 h to obtain a pre - esterification product; add 0.2 part of tetrabutyl titanate, continue to heat up to 250 °C, and at the same time reduce the pressure in the reaction kettle to 1 Pa, and react for 4 h to obtain a polycondensation product; cool the polycondensation product into strips through a casting machine and then cut it into particles by a pelletizer to obtain copolyester particles (3 mm); put the copolyester particles into a vacuum oven at 120 °C and dry for 4 h to obtain dried copolyester. Then, add the dried copolyester, 0.3 part of triphenyl phosphate and 0.1 part of tris(2,4 - di - tert - butylphenyl) phosphite into a twin - screw extruder and melt - extrude to obtain a melt; the feeding section temperature of the twin - screw extruder is 250 °C, the melting section temperature is 285 °C, the die head section temperature is 290 °C, use a hanger - type flat die head, the die lip width is 1.2 m, and the gap is 0.8 mm; quench the melt through a cooling roll at 30 °C to obtain a substrate layer with a thickness of 80 μm.

[0032] Under nitrogen protection, 45 parts of methyl methacrylate, 1.5 parts of divinylbenzene and 120 parts of deionized water were mixed, pre-emulsified at 60 °C for 30 min, 0.7 part of potassium persulfate initiator was added, the temperature was raised to 75 °C and reacted for 4 h to obtain a poly(methyl methacrylate) core emulsion; the poly(methyl methacrylate) core emulsion was diluted to a solid content of 10%, 12 parts of glycidyl methacrylate and 7 parts of styrene were added and reacted for 30 min, 0.5 part of potassium persulfate initiator was added dropwise, and after reacting at 70 °C for 6 h, it was centrifuged, washed and dried to obtain a core-shell toughening agent (the epoxy group content in the shell layer ≥ 10 mmol / g); 70 parts of polyurethane prepolymer and 10 parts of core-shell toughening agent were stirred and mixed at 90 °C for 30 min (500 rpm), 3 parts of photoinitiator Irgacure 184 was added and then ultrasonically dispersed (40 kHz, 15 min) to obtain a mixed solution, and the mixed solution was coated on the surface of the substrate layer using a microgravure coater, the coating thickness was 20 μm, then under the conditions of a wavelength of 365 nm and an intensity of 80 mW / cm 2 ultraviolet curing was carried out, the irradiation time was 2 min, and then it was cured in an oven at 60 °C for 1 h to obtain a toughening layer;

[0033] 15 parts of multi-walled carbon nanotubes were added to 30 wt% phosphoric acid solution (250 parts), ultrasonically treated at 60 °C in a constant temperature water bath for 2 h (300 W), and then washed and dried with deionized water to obtain phosphorylated carbon nanotubes; 60 parts of dimethyl terephthalate and 38 parts of 1,4-butanediol were added to a three-necked flask, the temperature was raised to 180 °C under nitrogen protection, 0.5 part of tetrabutyl titanate catalyst was added and reacted for 2 h, then the temperature was raised to 230 °C, the vacuum was reduced to 50 Pa, and the reaction was continued for 3 h, 1.2 parts of terminator ethylene glycol monomethyl ether (the molar ratio of hydroxyl group to carboxyl group is 1.2:1) was added, and reacted at 230 °C for 40 min to obtain a hydroxyl-terminated polyester oligomer; 30 parts of hydroxyl-terminated polyester oligomer was dissolved in 200 parts of xylene, 10 parts of phosphorylated carbon nanotubes were added, ultrasonically dispersed (250 W) at 120 °C for 1 h, 0.5 part of dicyclohexylcarbodiimide was added, the temperature was raised to 160 °C, and stirred (500 rpm) under nitrogen protection for 6 h (ester bond formation) to obtain a reaction solution; the reaction solution was hot filtered through a 0.45 μm filter membrane (80 °C), washed 3 times with xylene and acetone in turn to remove unreacted oligomers, and vacuum dried at 60 °C for 12 h to obtain modified carbon nanotubes; 10 parts of aramid nanofibers were swollen in 98 wt% concentrated sulfuric acid for 30 min, and washed with deionized water until neutral to obtain sulfuric acid swollen aramid nanofibers; 5 parts of modified carbon nanotubes, sulfuric acid swollen aramid nanofibers and 0.6 part of sodium dodecylbenzenesulfonate were added to 80 parts of N-methylpyrrolidone, and ball milled and dispersed for 4 h to obtain a spinning solution; electrospinning was carried out on the surface of the toughening layer under the conditions of a voltage of 17 kV, a receiving distance of 15 cm, and a solution flow rate of 0.8 mL / h to obtain an anti-tearing layer;

[0034] The isocyanate prepolymer Desmodur N3300, the silane coupling agent KH550 and the nano-silica sol were uniformly mixed according to a mass ratio of 7.5:1.5:1 to obtain a prepolymer mixture; the prepolymer mixture was uniformly sprayed on the surface of the tear-resistant layer using a high-pressure spray gun (nozzle diameter 0.3 mm, pressure 0.3 MPa), and the spraying amount was 7 g / m 2 , then in-situ polymerization was carried out at 50 °C for 20 min, and finally post-curing was carried out in an oven at 75 °C for 20 min to form an interfacial bonding layer with a thickness of 100 nm; then after preheating on a preheating roller at 95 °C for 3 min, longitudinal stretching and transverse stretching were carried out, and finally high-temperature shaping and cooling winding were carried out to obtain a polyester film with a thickness of 50 μm; the stretching ratio of longitudinal stretching was 3.8, the temperature was 105 °C, and the rate was 300% / min; the stretching ratio of transverse stretching was 4.3, the temperature was 115 °C, and the rate was 280% / min; the high-temperature shaping temperature was 180 °C and the time was 8 min; for cooling winding, it was first cooled to 100 °C at a rate of 5 °C / min, and then water-cooled at room temperature, and the winding tension was 2.5 N / cm 2 .

[0035] Examples 2 - 4

[0036] Referring to the preparation method and parameter conditions of Example 1, the specific differences are shown in Table 1; in Table 1, Temperature 1 is the reaction temperature for obtaining the pre-esterification product when preparing the copolyester particles; Temperature 2 and pressure are the reaction temperature and pressure for obtaining the polycondensation product when preparing the copolyester particles.

[0037] Comparative Example 1

[0038] Referring to the preparation method and parameter conditions of Example 1, the difference is that triphenyl phosphate was not added when preparing the substrate layer.

[0039] Comparative Example 2

[0040] Referring to the preparation method and parameter conditions of Example 1, the difference is that tris(2,4-di-tert-butylphenyl) phosphite was not added when preparing the substrate layer.

[0041] Comparative Example 3

[0042] Referring to the preparation method and parameter conditions of Example 1, the difference is that the copolyester particles were not dried when preparing the substrate layer.

[0043] Experimental Example 1 Toughness Test

[0044] The elongation at break was tested with reference to the standard of GB / T 1040.3 - 2006; the obtained results are shown in Table 1.

[0045] Table 1 Toughness Test of Examples 1 - 4 and Comparative Examples 1 - 3

[0046] Example Temperature 1 / °C Temperature 2 / °C Pressure / Pa Die Temperature / °C Elongation at Break / % Example 1 180 250 1 290 235 Example 2 185 255 4 300 237 Example 3 190 265 6 310 240 Example 4 200 280 10 320 236 Comparative Example 1 180 250 1 290 227 Comparative Example 2 180 250 1 290 224 Comparative Example 3 180 250 1 290 220

[0047] As can be seen from Table 1, in Examples 1-4, the copolyester main chain composed of rigid 2,6-naphthalenedicarboxylic acid and flexible 1,4-cyclohexanedimethanol forms an alternating distribution of ordered crystalline regions and amorphous regions, endowing the film with intrinsic tear resistance; among them, the molecular chain packing of the naphthalene ring structure enhances rigidity and resists the crack propagation caused by external forces; the helical conformation of the cyclohexane unit provides molecular chain ductility, dissipates energy through local slip, and prevents brittle fracture; the phosphate stabilizer optimizes the melt fluidity, inhibits processing defects, and the quenching process refines the crystal size and reduces structural weak points; in Example 3, when Temperature 1 is 190 °C, Temperature 2 is 265 °C, the pressure is 6 Pa, and the die head temperature is 310 °C, the prepared polyester film has the best toughness and the elongation at break is 240%. In Comparative Example 1, triphenyl phosphate was not added during the preparation of the base material layer, resulting in a decrease in the molecular chain spacing of the copolyester, a reduction in the free volume of the chain segments, and limited molecular chain movement leading to stress concentration and rapid crack propagation. Tris(2,4-di-tert-butylphenyl) phosphite achieves antioxidant protection by capturing free radicals and decomposing hydroperoxides. In Comparative Example 2, tris(2,4-di-tert-butylphenyl) phosphite was not added during the preparation of the base material layer. In the high-temperature section of the twin-screw extruder, a β-fracture reaction occurred in the copolyester main chain. After the copolyester main chain broke, the entanglement between molecular chains decreased. When the material was subjected to external forces, the molecular chains easily slid relative to each other and could not effectively transfer and disperse stress, resulting in a decrease in the film toughness. In Comparative Example 3, the copolyester particles were not dried during the preparation of the base material layer. At the extrusion temperature, acid-catalyzed hydrolysis occurred in the copolyester main chain, and water and degradation products (carboxylic acids, alcohols) volatilized during the quenching stage, and the formed micropores became stress concentration sources, reducing the film toughness.

[0048] Examples 5-7

[0049] Referring to the preparation method and parameter conditions of Example 3, the specific differences are shown in Table 2; in Table 2, Temperature 1 is the pre-emulsification temperature for preparing the core-shell toughening agent; Temperature 2 is the reaction temperature after adding 0.5 parts of potassium persulfate initiator during the preparation of the core-shell toughening agent.

[0050] Comparative Example 4

[0051] Referring to the preparation method and parameter conditions of Example 3, the difference is that after obtaining the polymethyl methacrylate core emulsion during the preparation of the core-shell toughening agent, its shell layer was not coated.

[0052] Comparative Example 5

[0053] Referring to the preparation method and parameter conditions of Example 3, the difference is that the core-shell toughening agent prepared in the present invention was replaced with KaneAce MX-125 of Nippon Kayaku.

[0054] Comparative Example 6

[0055] Referring to the preparation method and parameter conditions of Example 3, the difference is that no core-shell toughening agent was added when preparing the toughening layer.

[0056] Comparative Example 7

[0057] Referring to the preparation method and parameter conditions of Example 3, the difference is that after ultraviolet curing when preparing the toughening layer, it was not cured in an oven.

[0058] Toughness Test of Experimental Example 2

[0059] Referring to the standard of GB / T 1040.3-2006, the elongation at break and tensile strength were tested; the obtained results are shown in Table 2 and Figure 1 as follows.

[0060] Table 2 Toughness Tests of Example 3, Examples 5-7 and Comparative Examples 4-7

[0061]

[0062]

[0063] It can be seen from Table 2 and Figure 1 that in Example 3, Examples 5-7, the dynamically crosslinked polyurethane network formed by photocuring in the toughening layer has self-adaptive resilience, and the introduction of the core-shell toughening agent further enhances the energy absorption efficiency. When the film is subjected to external force, the reversible extension and fracture of the polyurethane molecular chains can consume a large amount of energy, and the core-shell structure dissipates energy synergistically through the fracture of the shell layer and the plastic deformation of the core body, delaying the material failure process; the dynamically crosslinked structure releases internal stress through bond reconstruction during repeated bending, avoiding the accumulation of permanent microscopic damage and endowing the film with excellent toughness; in Example 5, when the temperature one is 70 °C, the temperature two is 80 °C, the dosage of polyurethane prepolymer is 75 parts, and the dosage of shell toughening agent is 15 parts, the toughness of the prepared film is the best, and the tensile strength is 235 N / mm 2, the elongation at break is 244%. In Comparative Example 4, when preparing the core-shell toughening agent, after obtaining the polymethyl methacrylate core emulsion, its shell layer was not coated. Without the coating, there was no chemical bonding between the hard polymethyl methacrylate core and the polyurethane matrix (epoxy group content = 0), resulting in large-scale phase separation at the two-phase interface and damaging the stress transfer efficiency. In Comparative Example 5, the core-shell toughening agent prepared in the present invention was replaced with KaneAce MX-125 of Nippon Kayaku Co., Ltd. The reaction activity of MX-125 with isocyanate was lower than that of the core-shell toughening agent prepared in the present invention, resulting in a weak interface formed between the toughening agent and the matrix, and stress concentration was induced by large particle size particles in the matrix, accelerating crack initiation. In Comparative Example 6, no core-shell toughening agent was added when preparing the toughening layer. The polyurethane network had no second phase to initiate multiple crazes, and molecular chain slip dominated the fracture. In Comparative Example 7, after ultraviolet curing when preparing the toughening layer, it was not cured in an oven, so that the entangled network was not fully relaxed, resulting in a brittle response under impact load, and the unreacted Irgacure 184 photoinitiator decomposed to generate free radicals, initiating microdegradation of the material body and decreasing the toughness of the film.

[0064] Examples 8 - 10

[0065] Referring to the preparation method and parameter conditions of Example 5, the specific differences are shown in Table 3; the temperature in Table 3 is the temperature after raising the temperature for 2 h with the addition of 0.5 parts of tetrabutyl titanate catalyst when preparing the hydroxyl-terminated polyester oligomer.

[0066] Comparative Example 8

[0067] Referring to the preparation method and parameter conditions of Example 5, the difference is that the multi-walled carbon nanotubes were not phosphorylated when preparing the tear-resistant layer.

[0068] Comparative Example 9

[0069] Referring to the preparation method and parameter conditions of Example 5, the difference is that the phosphorylated carbon nanotubes were not surface-grafted with the hydroxyl-terminated polyester oligomer when preparing the tear-resistant layer.

[0070] Comparative Example 10

[0071] Referring to the preparation method and parameter conditions of Example 5, the difference is that the aramid nanofibers were not treated with sulfuric acid swelling when preparing the tear-resistant layer.

[0072] Comparative Example 11

[0073] Referring to the preparation method and parameter conditions of Example 5, the difference is that when preparing the modified carbon nanotubes, the reaction solution was not thermally filtered through a 0.45 μm filter membrane.

[0074] Example 12

[0075] Referring to the preparation method and parameter conditions of Example 5, the difference is that modified carbon nanotubes were not added when preparing the tear-resistant layer.

[0076] Example 13

[0077] Referring to the preparation method and parameter conditions of Example 5, the difference is that sulfuric acid-swollen aramid nanofibers were not added when preparing the tear-resistant layer.

[0078] Experimental Example 3 Toughness Test

[0079] The breaking strength was tested according to the standard of GB / T 16578-2009; the obtained results are shown in Table 3.

[0080] Table 3 Toughness Tests of Example 5, Examples 8-10, and Comparative Examples 8-13

[0081]

[0082] As can be seen from Table 3, in Examples 5 and 8-10, the tear-resistant layer adopts a composite system of aramid nanofibers and carbon nanotubes grafted on the surface, and a highly oriented nanofiber network is constructed through the electrospinning process. The high specific surface area of the nanoscale aramid fibers enhances the interfacial bonding force and forms a continuous force transmission path; the hydroxyl groups grafted with polyester oligomers on the modified carbon nanotubes enable them to be evenly dispersed and penetrate into the fiber gaps, and inhibit the spread of microdamage through crack bridging and pull-out effects; at the same time, the nanoscale reinforcing agent significantly reduces the density of the material, and endows the film with the characteristics of lightweight and high strength without significantly increasing the thickness. This nano-synergistic reinforcement mechanism significantly improves the toughness of the polyester film. In Example 8, when the temperature is 240 °C, the amount of aramid nanofibers is 12 parts, the amount of modified carbon nanotubes is 8 parts, and the electrospinning voltage is 20 kV, the toughness of the prepared film is the best, and the fracture strength is 229 MPa. In Comparative Example 8, when preparing the tear-resistant layer, the multi-walled carbon nanotubes were not phosphorylated. When subjected to external forces, the carbon nanotubes could not effectively disperse and transfer stress, and could not fully play their reinforcing role, resulting in a decrease in the toughness of the film. In Comparative Example 9, when preparing the tear-resistant layer, the phosphorylated carbon nanotubes were not surface-grafted with hydroxyl-terminated polyester oligomers. The carbon nanotubes were prone to agglomeration in the spinning solution, forming stress concentration points. When the film was torn by external forces, these agglomerated carbon nanotubes could not evenly bear the stress, easily leading to the rapid propagation of cracks and making the toughness of the film poor. Sulfuric acid swelling treatment can increase the molecular chain spacing of aramid nanofibers, expose more active groups, and is beneficial to better combination with other components. In Comparative Example 10, when preparing the tear-resistant layer, the aramid nanofibers were not subjected to sulfuric acid swelling treatment, resulting in a reduction in the interfacial contact area between the fibers and the modified carbon nanotubes. The fibers were prone to relative sliding and could not effectively prevent the propagation of cracks, thereby reducing the toughness of the film. In Comparative Example 11, when preparing the modified carbon nanotubes, the reaction solution was not hot-filtered through a 0.45 μm filter membrane, and impurity defects caused stress concentration and accelerated crack initiation. In Comparative Example 12, when preparing the tear-resistant layer, the modified carbon nanotubes were not added, and the aramid fiber composite material lacking carbon nanotubes could not form a hierarchical reinforcement structure (in the original design, the fibers bear macroscopic loads and the carbon nanotubes inhibit microcracks), resulting in a decrease in toughness. In Comparative Example 13, when preparing the tear-resistant layer, the sulfuric acid-swollen aramid nanofibers were not added, and a three-dimensional mechanical skeleton could not be constructed. Moreover, the randomly distributed unoriented carbon nanotubes led to the loss of film anisotropy and a decrease in toughness.

[0083] Examples 11-13

[0084] Referring to the preparation method and parameter conditions of Example 8, the specific differences are shown in Table 4; the mass ratio of the three in Table 4 is the mass ratio of the isocyanate prepolymer Desmodur N3300, the silane coupling agent KH550, and the nano-silica sol.

[0085] Comparative Example 14

[0086] Referring to the preparation method and parameter conditions of Example 8, the difference is that in-situ polymerization was not carried out when preparing the interfacial bonding layer.

[0087] Comparative Example 15

[0088] Referring to the preparation method and parameter conditions of Example 8, the difference is that nano-silica sol was not added when preparing the interfacial bonding layer, the dosage of isocyanate prepolymer Desmodur N3300 was 15 parts, and the dosage of silane coupling agent KH550 was 3 parts.

[0089] Comparative Example 16

[0090] Referring to the preparation method and parameter conditions of Example 8, the difference is that the wet film thickness was 100 μm when preparing the interfacial bonding layer.

[0091] Comparative Example 17

[0092] Referring to the preparation method and parameter conditions of Example 8, the difference is that post-curing was not carried out after in-situ polymerization when preparing the interfacial bonding layer.

[0093] Experimental Example 4 Toughness Test

[0094] The fracture strength was tested according to the standard of GB / T 16578-2009; the obtained results are shown in Table 4.

[0095] Table 4 Toughness Test of Example 8, Examples 11 - 13 and Comparative Examples 14 - 17

[0096] Example Mass Ratio of the Three <![CDATA[Spraying amount / g / m 2 > Post-Curing Time / min Tensile Strength / MPa Example 8 7.5:1.5:1 7 20 229 Example 11 7.5:1.5:2 9 30 234 Example 12 7.5:1.5:3 11 40 232 Example 13 7.5:1.5:4 9 50 230 Comparative Example 14 7.5:1.5:1 7 20 209 Comparative Example 15 / 7 20 217 Comparative Example 16 7.5:1.5:1 7 20 201 Comparative Example 17 7.5:1.5:1 7 / 211

[0097] As can be seen from Table 4, in Example 8 and Examples 11 - 13, the interfacial bonding layer significantly improves the interlayer bonding efficiency through a multi-stage chemical cross-linking and nano-reinforcement strategy. The isocyanate prepolymer forms a dense covalent network with the hydroxyl groups on the surface of the tear-resistant layer, anchoring the reinforcing phase and the matrix to prevent failure caused by interfacial peeling; the silane coupling agent further bridges the inorganic nano-silica sol and the organic phase to construct a molecular-level interpenetrating structure through an in-situ condensation reaction to disperse local stress; the nano-silica sol fills the interfacial micropores and forms a physical interlock to delay the crack propagation rate when crossing the interface; the dynamic cross-linking system endows the interface with self-adaptive deformation ability, consuming energy through bond reconstruction under external force to avoid delamination caused by stress concentration and improving the toughness of the polyester film. In Example 11, when the mass ratio of the three is 7.5:1.5:2 and the spraying amount is 9 g / m 2, when the post-curing time is 30 min, the obtained film has the best toughness and the fracture strength is 234 MPa. In Comparative Example 14, in-situ polymerization was not carried out when preparing the interfacial bonding layer, and the prepolymer mixture could not fully react to form a stable polymer network, resulting in insufficient cohesive force of the interfacial bonding layer and insufficient bonding strength with the tear-resistant layer. When subjected to external force, cracks are likely to propagate at the interface, thereby reducing the toughness of the film. Nano-silica sol has a high specific surface area and activity and can fill the voids in the polymer network, playing a role in strengthening and toughening. In Comparative Example 15, nano-silica sol was not added when preparing the interfacial bonding layer, and the strength and toughness of the interfacial bonding layer would decrease, and its ability to resist tearing would be weakened; moreover, due to the lack of filling and strengthening effect of nano-silica sol, the interfacial bonding layer is more likely to deform and rupture when subjected to external tensile force, thereby affecting the toughness of the film. In Comparative Example 16, the wet film thickness was 100 μm when preparing the interfacial bonding layer. A thicker wet film would result in uneven stress distribution inside the interfacial bonding layer and incomplete curing or internal defects. These defects would become stress concentration points, and when the film was subjected to a tearing force, it was easy to rupture from these weak parts, thereby reducing the toughness of the film. Through post-curing, these groups can fully react, increasing the crosslinking density and molecular weight of the polymer, thereby enhancing the mechanical properties of the interfacial bonding layer. In Comparative Example 17, post-curing was not carried out after in-situ polymerization when preparing the interfacial bonding layer, and the strength and stability of the interfacial bonding layer would be insufficient, and it was easy to be damaged and torn when subjected to external force.

[0098] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a tear-resistant and high-toughness functional polyester film, characterized in that: The preparation method is as follows: copolyester particles, triphenyl phosphate and tris(2,4-di-tert-butylphenyl) phosphite are melt-extruded and then quenched through a cooling roller to obtain a substrate layer; a mixed solution of a polyurethane prepolymer, a core-shell toughening agent and a photoinitiator is coated on the surface of the substrate layer using a micro-gravure coater to obtain a toughening layer; electrostatic spinning is performed on the surface of the toughening layer to obtain a tear-resistant layer; a prepolymer mixed solution is uniformly sprayed on the surface of the tear-resistant layer using a high-pressure spray gun to obtain an interface bonding layer, and then after preheating on a preheating roller, longitudinal stretching and transverse stretching are performed, and finally high-temperature shaping and cooling and rolling are performed to obtain the polyester film; The copolyester particles are prepared from 1,4-cyclohexanedimethanol, 2,6-naphthalene dicarboxylic acid and terephthalic acid; The prepolymer mixed liquid is prepared from isocyanate prepolymer, silane coupling agent KH550 and nano silica sol.

2. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 1, characterized in that: The preparation process of the substrate layer is as follows: the copolyester particles are placed in a vacuum oven at 120° C. and dried for 4 hours to obtain a dry copolyester, and then the dry copolyester, the triphenyl phosphate and the tris(2,4-di-tert-butylphenyl) phosphite are added to a twin-screw extruder for melt extrusion to obtain a melt; the die section temperature of the twin-screw extruder is 290-320° C.; the melt is quenched to obtain the substrate layer.

3. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 2, characterized in that: The copolyester particle preparation process is as follows: adding the 1,4-cyclohexanedimethanol, the 2,6-naphthalene dicarboxylic acid and the terephthalic acid into a reaction kettle, introducing nitrogen into the reaction kettle, heating to 180-200° C. and reacting for 2.5 hours to obtain a pre-esterified product; The temperature is continued to be raised to 250-280° C., while the pressure in the reactor is reduced to 1-10 Pa, and the reaction is carried out for 4 hours to obtain a polycondensation product; the polycondensation product is cooled into strips and cut into particles to obtain the copolyester particles.

4. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 1, characterized in that: The preparation process of the toughening layer is as follows: 70-85 parts of the polyurethane prepolymer and 10-25 parts of the core-shell toughening agent are stirred and mixed at 90°C for 30 minutes, the photoinitiator is added and ultrasonically dispersed to obtain a mixed liquid, the mixed liquid is coated on the surface of the substrate layer using the micro-gravure coater, followed by UV curing, and then ripened in a 60°C oven for 1 hour to obtain the toughening layer.

5. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 4, characterized in that: The core-shell toughening agent preparation process is as follows: under nitrogen protection, methyl methacrylate, divinylbenzene and deionized water are mixed, pre-emulsified at 60-80°C, potassium persulfate initiator is added, the temperature is raised to 75°C for reaction for 4 hours, and polymethyl methacrylate core emulsion is obtained; the polymethyl methacrylate core emulsion is diluted to a solid content of 10%, glycidyl methacrylate and styrene are added for reaction for 30 minutes, the potassium persulfate initiator is added dropwise, the reaction is carried out at 70-95°C for 6 hours, and then centrifuged, washed and dried to obtain the core-shell toughening agent.

6. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 1, characterized in that: The preparation process of the tear-resistant layer is as follows: 10-15 parts of aramid nanofibers are swelled in concentrated sulfuric acid for 30 minutes, and washed with deionized water until neutral to obtain sulfuric acid-swollen aramid nanofibers; 5-10 parts of modified carbon nanotubes, the sulfuric acid-swollen aramid nanofibers and 0.6 parts of sodium dodecylbenzene sulfonate are added to 80 parts of N-methylpyrrolidone, and ball milling dispersion is performed to obtain a spinning solution; the electrostatic spinning is performed on the surface of the toughening layer at a voltage of 17-25 kV to obtain the tear-resistant layer.

7. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 6, characterized in that: The modified carbon nanotube preparation process is as follows: adding multi-walled carbon nanotubes to a phosphoric acid solution, ultrasonically treating in a constant temperature water bath at 60°C, then washing with deionized water and drying to obtain phosphorylated carbon nanotubes; adding dimethyl terephthalate and 1,4-butanediol into a three-necked flask, heating to 180°C under nitrogen protection, adding a catalyst tetrabutyl titanate to react for 2h, then heating to 230-255°C, reducing the vacuum degree to 50Pa, continuing the reaction for 3h, adding a terminator ethylene glycol monomethyl ether, reacting at 230°C to obtain a hydroxyl-terminated polyester oligomer; dissolving the hydroxyl-terminated polyester oligomer in xylene, adding the phosphorylated carbon nanotubes, ultrasonically dispersing at 120°C, adding dicyclohexylcarbodiimide, heating to 160°C, stirring under nitrogen protection to obtain a reaction solution; and filtering the reaction solution through heat to obtain the modified carbon nanotubes.

8. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 1, characterized in that: The preparation process of the interface bonding layer is as follows: the isocyanate prepolymer, the silane coupling agent KH550 and the nano silica sol are mixed uniformly in a mass ratio of 7.5:1.5:1-4 to obtain the prepolymer mixed liquid; the prepolymer mixed liquid is uniformly sprayed on the surface of the anti-tear layer using the high-pressure spray gun, and the spraying amount is 7-11g / m 2 , followed by in-situ polymerization at 50° C. for 20 min, and finally post-curing in an oven at 75° C. for 20-50 min to form the interface bonding layer with a thickness of 100 nm.

9. The process for preparing a tear-resistant and high-toughness functional polyester film according to claim 1, characterized in that: The longitudinal stretching has a stretching ratio of 3.8, a temperature of 105°C, and a rate of 300% / min; the transverse stretching has a stretching ratio of 4.3, a temperature of 115°C, and a rate of 280% / min; the high temperature setting temperature is 180°C, and the time is 8 minutes; the cooling and winding first decreases to 100°C at a rate of 5°C / min, and then is water-cooled at room temperature, and the winding tension is 2.5N / cm 2 .

10. A tear-resistant and high-toughness functional polyester film, characterized in that: The polyester film consists of a substrate layer, a toughening layer, an anti-tearing layer and an interface bonding layer; the polyester film is prepared by the preparation process described in any one of claims 1-9.

Citation Information

Patent Citations

  • Polyester film and process for producing the same

    CA2084684A1

  • Polyester film, and solar-cell back sheet and solar cell each including same

    CN102470653A

  • Aramid 1313 / MWCNT (Multi-Walled Carbon Nanotube) nano fibers and preparation method thereof

    CN102877152A

  • Para-aramid nanofiber membrane and preparation method thereof

    CN110373814A

  • Fiber-reinforced wear-resistant TPU composite material and preparation method thereof

    CN118562283A

Cited By

  • Method for preparing high-elasticity polyester fiber fabric through polyester regeneration

    CN121228394A